2006
DOI: 10.4049/jimmunol.177.10.7131
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella bronchiseptica Modulates Macrophage Phenotype Leading to the Inhibition of CD4+ T Cell Proliferation and the Initiation of a Th17 Immune Response

Abstract: Bordetella bronchiseptica is a Gram-negative bacterium equipped with several colonization factors that allow it to establish a persistent infection of the murine respiratory tract. Previous studies indicate that B. bronchiseptica adenylate cyclase toxin (ACT) and the type III secretion system (TTSS) synergize to drive dendritic cells into an altered phenotype to down-regulate the host immune response. In this study, we examined the effects of B. bronchiseptica ACT and TTSS on murine bone marrow-derived macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 47 publications
(62 reference statements)
4
44
0
1
Order By: Relevance
“…These data are also in agreement with that obtained in mice, in which vaccination with a whole cell pertussis vaccine, known to contain LOS in high concentration, promotes the expansion of IL-17-producing T cells dependent on TLR4 signaling, as well as expansion of Th1 cells (48). It has also been shown that B. bronchiseptica induces a strong Th17 immune response both in vitro and in vivo (40). IL-17-producing T cells may determine in patients a sustained inflammation of the airways causing cough, as reported for other respiratory infections (49).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These data are also in agreement with that obtained in mice, in which vaccination with a whole cell pertussis vaccine, known to contain LOS in high concentration, promotes the expansion of IL-17-producing T cells dependent on TLR4 signaling, as well as expansion of Th1 cells (48). It has also been shown that B. bronchiseptica induces a strong Th17 immune response both in vitro and in vivo (40). IL-17-producing T cells may determine in patients a sustained inflammation of the airways causing cough, as reported for other respiratory infections (49).…”
Section: Discussionsupporting
confidence: 80%
“…We have previously demonstrated that incubation of human MDDC with B. pertussis induced a Th1 predominant polarization and expression of IL-23, involved in Th17 cell expansion, in the absence of the Th1-inducing cytokine IL-12p70 (21,22). Furthermore, evidence is accumulating to show that Bordetella infection might bias the host response toward a Th17 response (40,41). In this study, novel data support this view.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, the priming of Ag-specific Th17 cells and/or Ag-induced IL-17A production of isolated effector cells has been reported for many pathogens, including intra-and extracellular bacteria, fungi, viruses and parasites, but in most cases the Th17/IL-17A response does not exceed the Th1/IFN-g response (22)(23)(24)(25)(32)(33)(34). It has been suggested that intestinal Citrobacter rodentium and pulmonary Bordetella bronchiseptica infections induce a dominant Th17 cell response, but this has been observed after nonspecific restimulation with PMA/ionomycin (35) or the cellular source of IL-17A has not been defined (36).…”
Section: Discussionmentioning
confidence: 98%
“…immunization has important implications in the context of optimizing rational vaccine design. However, it is critical to consider that there are also reports showing a negative influence of IL-17 on the outcome of immune responses (23). Therefore, it would be essential to carefully evaluate and weight both advantages and potential risks on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%